2016
DOI: 10.1155/2016/8797206
|View full text |Cite
|
Sign up to set email alerts
|

HDAC Inhibitors as Epigenetic Regulators of the Immune System: Impacts on Cancer Therapy and Inflammatory Diseases

Abstract: Histone deacetylase (HDAC) inhibitors are powerful epigenetic regulators that have enormous therapeutic potential and have pleiotropic effects at the cellular and systemic levels. To date, HDAC inhibitors are used clinically for a wide variety of disorders ranging from hematopoietic malignancies to psychiatric disorders, are known to have anti-inflammatory properties, and are in clinical trials for several other diseases. In addition to influencing gene expression, HDAC enzymes also function as part of large, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
214
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(230 citation statements)
references
References 145 publications
6
214
0
Order By: Relevance
“…On the contrary, histone deacetylases (HDAC) remove acetyl groups from histones, thereby tightening the chromatin structure, which hinders binding of transcription factors and hence suppress gene transcription. Numerous studies demonstrated that HDAC inhibitors have therapeutic potential to treat diseases such as cancer, inflammation, fibrosis and even cognitive disorders (Eckschlager et al, 2017;Fischer et al, 2010;Hull et al, 2016;Liu et al, 2015).…”
Section: Histone Deacetylases (Hdac)mentioning
confidence: 99%
“…On the contrary, histone deacetylases (HDAC) remove acetyl groups from histones, thereby tightening the chromatin structure, which hinders binding of transcription factors and hence suppress gene transcription. Numerous studies demonstrated that HDAC inhibitors have therapeutic potential to treat diseases such as cancer, inflammation, fibrosis and even cognitive disorders (Eckschlager et al, 2017;Fischer et al, 2010;Hull et al, 2016;Liu et al, 2015).…”
Section: Histone Deacetylases (Hdac)mentioning
confidence: 99%
“…This class includes azacitidine (AZA) and decitabine (DEC: 5‐aza‐2'‐deoxycytidine), which are hypomethylating prodrugs whose active triphosphate forms are incorporated into RNA and DNA, respectively, and induce hypomethylation of the DNA (DEC) and ribosomal disassembly and disruption of protein translation (AZA) . Another group of epigenetic modifiers includes inhibitors of histone deacetylase, such as panabinostat, which prevent the deacetylation of histone and nonhistone proteins resulting in alterations of both gene transcription and protein activity …”
Section: Posttransplant Therapymentioning
confidence: 99%
“…Panobinostat is a potent oral nonselective histone deacetylase inhibitor with preclinical activity in myeloid malignancies . The phase I/II PANOBEST trial evaluated maintenance panabinostat for 42 high‐risk MDS and AML patients following RIC allo‐HSCT for up to 1 year.…”
Section: Posttransplant Therapymentioning
confidence: 99%
“…Epigenetic modification in gene expression and cellular responses by histone deacetylase (HDAC) has gained much attention in recent years and HDAC inhibitors have been tested to treat various diseases [7,8]. Currently, 18 mammalian HDACs have been identified and grouped into 4 classes (Class I: HDAC1, HDAC2, HDAC3, and HDAC8; Class IIa: HDAC4, HDAC5, HDAC7, and HDAC9; Class IIb: HDAC6 and HDAC10; Class III: sirtuins 1-7; Class IV: HDAC11) [9].…”
Section: Introductionmentioning
confidence: 99%